Digital-Based Change Management for Enhancing Vocational Students’ Work Readiness - Muhtadin, Muhtadin; Hasanah, Enung; Sukirman, Sukirman (JURNAL AL-TANZIM, 2026)
This study aims to develop a digital-based change management model to enhance vocational students’ work readiness in vocational schools. Rapid technological change and evolving industry requirements have intensified the mismatch between vocational graduates’ competencies and labor market expectations. Previous studies highlight that limited digital integration and weak change management reduce the relevance of vocational education. This research employed a qualitative case study involving school leaders, vocational teachers, industry partners, and students. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed thematically using Atlas. Ti 9. The findings indicate that effective digital transformation is shaped by six interrelated factors: the urgency for change, school–industry collaboration, continuous teacher competency development, technology-embedded curriculum implementation, systematic evaluation mechanisms, and graduate outcomes. These factors collectively strengthen students’ technical skills, digital literacy, and employment-readiness. The proposed model demonstrates that adaptive change management and active stakeholder involvement improve curriculum relevance and perceived employability. This study contributes theoretically by enriching perspectives on change management in vocational education and, practically, by offering a contextual framework for digital curriculum development. It recommends continuous curriculum updating, infrastructure investment, and sustained industry partnerships to ensure long-term workforce readiness.